Trinidad and Tobago : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues Paper focuses on the Heritage and Stabilization Fund (HSF) and development in the energy sector in Trinidad and Tobago. The HSF, established in 2007, is an important national asset, which has broad-based political and social support. The HSF has developed a strong record since its creation. It has performed well as measured by the accumulation of savings, the portfolio return, and adherence to the Santiago Principles for transparency and governance. This is particularly commendable given global and domestic financial crises.